Youth Participation in the Prevention of Regional Head Election Violations in the Contestation Dimension in Baubau City - Zubair; Satria, Eko; Supriyanto, Hadi; Zidan, Alwan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
Youth participation is crucial in emerging democracies in Baubau City, where political knowledge and understanding are limited. Identity politics, including ethnicity and culture, often dominate conflicts, leading to collective frustration and dissatisfaction. The challenge of involving youth in political participation is not only mobilizing contestants but also assisting organizers in monitoring the course of the upcoming regional head elections. This research aims to direct the role of youth through participatory movements towards efforts to prevent violations in the dimension of contestation, specifically in the right to be elected, which may result in potential social insecurity in the community. This research uses normative legal research. Methodologically, this research is descriptive qualitative. The author uses data collection techniques with library research. The author's data analysis technique in this research uses logical and systematic analysis. The conclusion of this research is that youth voter participation is decreasing due to the disconnect between the political process and pressing issues. To empower the next generation, understanding the determinants and implementing outreach initiatives can empower them. Youth participation in regional elections, education, socialization programs, and the formation of cross-identity communities can prevent violations of identity politics and increase solidarity between different groups.